On the return of Calyptospadix cerula (Hydrozoa:Bougainvilliidae) to Santa Marta’s Ciénaga Grande lagoon, in the Colombian Caribbean - León, Ricardo Álvarez (Arquivos de Ciências do Mar, 2017)
Calyptospadix cerula Clarke 1882, an estuarine hidrozoarian species which had been registered in 1973 only in the northern zone of the Ciénaga Grande of Santa Marta (Colombia), was then reported in December of 1985, after lingering periods of sweetening and hipersalinization of the ciénaga for the western side. In contrast to the organisms presente in the north, those found on the western side tolerate more severe salinity and temperature conditions, which range 0 – 46 ups and 27 - 36oC.